La Forêt du Refuge à la Maison Mazel, dans les Cévennes - Jacques Verseils (Diasporas: Circulations, Migrations, Histoire)
The home of the Camisard prophet Abraham Mazel located in the Cévennes now hosts the Abraham Mazel association. Dedicated to resistance in the past and present, the association’s project is to offer on its grounds a «Refuges’ forest», allowing the visitor to travel symbolically across the diversity of the Huguenot diaspora’s land.